The Pharmacodynamics of Antipsychotic Drugs in Women and Men - Seeman, Mary V. (Frontiers in Psychiatry, 2021)
Background: Animal and human experiments have confirmed sex differences in the expression of hepatic enzymes that metabolize antipsychotic drugs and that may, in this way, be partly responsible for the clinical sex/gender differences observed in the efficacy and tolerability of antipsychotic treatment. Aim: The aim of this mini review is to synthesize the literature on the pharmacodynamics of male/female differential response to antipsychotic drugs. Method: Relevant search terms were used to search for pre-clinical and human trials and analysis of antipsychotic differential drug response and occurrence/severity of adverse effects in women and men. Results: The search found that sex influences drug response via the amount of a given drug that enters the brain and the number of neurotransmitter receptors to which it can bind. Consequently, sex partly determines the efficacy of a specific drug and its liability to induce unwanted effects. There are other factors that can overshadow or enhance the dimorphic effect of sex, for instance, the host's age, hormonal status, diet and life style as well as the molecular structure of the drug and its dose, and the method of its administration. Most of all, the host's individual genetics affects each step of a drug's pharmacodynamics. Conclusion: On average, women's psychotic symptoms respond to antipsychotic drugs at doses lower than men's. This means that many women may be de facto overdosed and, thus, experience unnecessary adverse effects. That being said, factors such as genetics and age probably determine drug response and tolerability to a greater degree than do biological sex or gender social roles.